ICARDA and SAHARA & Sahel Observatory: Building Resilient Pastoral Systems - Frija, Aymen (ICARDA Communication Team, 2023)
ICARDA scientists recently met with The Sahara and Sahel Observatory (OSS) team of experts to discuss the potential of collaboration in research on pastoral systems and adaptation to address climate change impacts on rural farmers. The OSS initiates and facilitates partnerships on common challenges related to the management of shared water resources and the implementation of international agreements on desertification, biodiversity, and climate change in Africa.